Role of Jasmonates, Calcium, and Glutathione in Plants to Combat Abiotic Stresses Through Precise Signaling Cascade - Aslam, Saima; Gul, Nadia; Mir, Mudasir A.; Asgher, Mohd.; Al-Sulami, Nadiah; Abulfaraj, Aala A.; Qari, Sameer (Frontiers in Plant Science, 2021)
Plant growth regulators have an important role in various developmental processes during the life cycle of plants. They are involved in abiotic stress responses and tolerance. They have very well-developed capabilities to sense the changes in their external milieu and initiate appropriate signaling cascade that leads to activation of plant defense mechanisms. The plant defense system activation causes build-up of plant defense hormones like jasmonic acid (JA) and antioxidant system like glutathione (GSH). Moreover, calcium (Ca2+) transients are also seen during abiotic stress conditions depicting the role of Ca2+ in alleviating abiotic stress as well. Therefore, these growth regulators tend to control plant growth under varying abiotic stresses by regulating its oxidative defense and detoxification system. This review highlights the role of Jasmonates, Calcium and glutathione in abiotic stress tolerance and activation of possible novel interlinked signaling cascade between them. Further, phyto-hormone crosstalk with jasmonates, calcium and glutathione under abiotic stress conditions following with brief insights on omics approaches is also elucidated.